2019
DOI: 10.1002/msc.1403
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study comparing regular care with a nurse‐led clinic based on tight disease activity control and person‐centred care in patients with rheumatoid arthritis with moderate/high disease activity: A 6‐month evaluation

Abstract: IntroductionA recent survey showed that 27% of rheumatoid arthritis (RA) patients had inadequately controlled disease activity. Hence, there is a need for new strategies aiming at improving patient outcomes. The aim of the present study was to evaluate the effect of a nurse‐led clinic with frequent visits, treat‐to‐target and person‐centred care of patients with established RA and moderate‐to‐high disease activity compared with patients receiving regular care.MethodsThe study was a randomized, controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Outcomes from these trials were increased self-efficacy1319252627; improved experience of health111720; improved satisfaction with care10; improved symptom control1720222829; improved physical function/capacity11172021; improved activities of daily living24; fewer chronic heart failure/chronic obstructive pulmonary disease related deteriorations13; improved discharge planning30; shorter length of hospital stay232431; and cost saving 32. In six trials results were not significant in the ITT analysis (no data on PP available) 91112141516…”
Section: Outcomes and Evidencementioning
confidence: 99%
“…Outcomes from these trials were increased self-efficacy1319252627; improved experience of health111720; improved satisfaction with care10; improved symptom control1720222829; improved physical function/capacity11172021; improved activities of daily living24; fewer chronic heart failure/chronic obstructive pulmonary disease related deteriorations13; improved discharge planning30; shorter length of hospital stay232431; and cost saving 32. In six trials results were not significant in the ITT analysis (no data on PP available) 91112141516…”
Section: Outcomes and Evidencementioning
confidence: 99%
“…The current EULAR recommendations for the treatment of RA include the involvement of specialist nurses in the follow-up of patients with RA. 8 Nurse-led care (NLC) has already been successfully established in some countries (eg, the UK, the Netherlands, Denmark and Sweden), [9][10][11][12][13][14] showing evidence of non-inferiority of NLC in comparison to RLC in different clinical settings. 11 Furthermore, evidence suggests an added value of a holistic perspective and an increased focus on individual patients needs, and this has been shown to be appreciated by patients.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…The Fransen trial [27] (two groups, established RA, 6month treatment) only reported LDA; significantly more patients achieved LDA with intensive than conventional treatment (31% vs 16%, p = 0.028). Similarly, the Bergsten trial [28] reported a greater proportion of patients achieved LDA with intensive (48%) than conventional treatment (24%). The van Hulst trial [22] (two groups, early and established RA, 18month treatment) reported more EULAR good responders (which includes LDA) with intensive (22%) than conventional treatment (18%) (significance unreported).…”
Section: Ttt Vs Usual Carementioning
confidence: 91%
“…Eight trials (1977 patients) compared TTT with usual care [22][23][24][25][26][27][28][29]; seven trials (2418 patients) compared different treatment protocols [30][31][32][33][34][35][36]; six trials (1758 patients) compared different treatment targets [24,26,35,[37][38][39]; four trials (1143 patients) made other comparisons of conventional with intensive therapy [14,17,19,20]. Thirteen trials studied early RA patients [17,24,25,[30][31][32][33][34][35][36][37][38][39]; five studied established RA patients [19,[26][27][28]40]; and four studied early and established RA [20,22,23,29]. Fifteen trials involved controls receiving less intensive treatment…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation